Financial Performance Of Pertamina Indonesia Against Saudi Aramco, Petro China And Exxon Mobil Usa In Price’s Turmoil Years - Sazly, Syukron (LPPM Universitas Bina Sarana Informatika, 2023)
This year, PT Pertamina (Persero) has re-emerged as the only Indonesian company to be included in the Fortune Global 500 list. PT. Pertamina managed to increase its ranking from position 287 last year to position 223 this year. While several global oil companies are considered to have performed better so that they are in a position far above Pertamina, namely, SAUDI ARAMCO is ranked 18th, Petro China is ranked 19th and Exxon Mobil is ranked 23rd. and last situation. Longer historical data is needed to assess the performance of these companies more fairly, not only looking at the profitability aspect but also other aspects such as liquidity, solvency and productivity of these companies. This study aims to compare the financial performance of the four oil companies based on data for 2017-2021. This type of research is descriptive quantitative, using a purposive sampling technique with certain considerations. The sample used is the 2017-2021 financial performance of 24 samples. Data processing uses SPSS 25, with the Kruskall Wallis test. Variables compared are Liquidity Ratio (Current Ratio /CR), Solvability (Debt-Equity Ratio /DER), Activity (Total Asset Trurn Over /TATO), Profitability (Net Profit Margin / NPM), Dupont Ratio (Return On Investment / ROI ) and Return On Assets / ROE). The results show that there are significant differences in the Liquidity Ratio (CR), Solvency Ratio (DER). Activity Ratio (TATO) and Dupont Ratio (Return On Investment/ROI) on the company's financial performance between Pertamina and Saudi Aramco, Petro China and Exxon Mobil. Meanwhile, the Profitability Ratio (NPM) and the Dupont Ratio (Return On Equity / ROE) are not significantly different.